2016
DOI: 10.24191/abrij.v2i2.10027
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Entrepreneurial Competencies and Business Success of Malaysian SMEs: The Mediating Role of Innovation and Brand Equity

Abstract: This conceptual paperis to study the relationship         of         entrepreneurial competencies on business success in the context of Malaysian SMEs. Inthe recent study, when the business environment is hostile and dynamic, the entrepreneurial competencies are identified as the most important factor in business success. Entrepreneurial competencies are also connected directly to business performance.Beside     entrepreneurial competencies, the entrepreneurs should also be competent to create an innovation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Strategies act as a bridge to join firms' resources and capability (Ahmad et al, 2010;Parnell, Lester & Menefee, 2000). Many studies have either conceptualised or found the positive influence of strategic competency for achieving superior performances (Nakhata, 2018;Suhaimi et al, 2018;Umar & Ngah, 2017;Yusuff et al, 2016). We thus hypothesise, H1a: There is a positive impact of strategic competency on business growth among Malay entrepreneurs.…”
Section: Development Of Hypotheses H1: Impact Of Strategic Competencymentioning
confidence: 99%
See 4 more Smart Citations
“…Strategies act as a bridge to join firms' resources and capability (Ahmad et al, 2010;Parnell, Lester & Menefee, 2000). Many studies have either conceptualised or found the positive influence of strategic competency for achieving superior performances (Nakhata, 2018;Suhaimi et al, 2018;Umar & Ngah, 2017;Yusuff et al, 2016). We thus hypothesise, H1a: There is a positive impact of strategic competency on business growth among Malay entrepreneurs.…”
Section: Development Of Hypotheses H1: Impact Of Strategic Competencymentioning
confidence: 99%
“…Alternatively, entrepreneurial learning is considered a core entrepreneurial competency. Many studies have found the positive influence of learning competency on performance (Nakhata, 2018;Umar & Ngah, 2017;Yusuff et al, 2016). Thus:…”
Section: H3: Impact Of Learning Competency On Business Growthmentioning
confidence: 99%
See 3 more Smart Citations